(untitled) (Research, Society and Development, 2021)
The present work aimed to outline the profile of the most common forms of identification and / or post mortem recognition in the IML of Marabá / PA in the years 2016 and 2017. It is a scientific, transversal, nominal study of the observational type, of descriptive character, aimed at documentary analysis of expert reports at the Renato Chaves Expertise Center in which they were anthropological, documentary identification and ultimately DNA identification. The data were analyzed using scatter plots (ANOVA) and a representation of comparison of means (Tukey test) in the R Studio® software. 735 reports for the year 2016 and 758 reports for 2017 were analyzed. In 2016, the most used identification / recognition methods were For identification by means of corpse documents and identification by means of documents combined with family recognition; DNA identification corresponded to 3.12%. In 2017, the most used methods were also documents from the corpse and identification through documents combined with family recognition; DNA analysis corresponded to 6.20%. The most common forms of post-mortem identification in the IML of Marabá / PA were those that use sign photography, typing and bioanthropology; post-mortem identification by DNA analysis was significantly low.